A New Method to Calibrate Attachment Angles of Data Loggers in Swimming Sharks. (29th September 2009) - Kawatsu, Shizuka; Sato, Katsufumi; Watanabe, Yuuki; Hyodo, Susumu; Breves, Jason P.; Fox, Bradley K.; Grau, E. Gordon; Miyazaki, Nobuyuki
Abstract : Recently, animal-borne accelerometers have been used to record the pitch angle of aquatic animals during swimming. When evaluating pitch angle, it is necessary to consider a discrepancy between the angle of an accelerometer and the long axis of an animal. In this study, we attached accelerometers to 17 free-ranging scalloped hammerhead shark ( Sphyrna lewini ) pups from Kaneohe Bay, Hawaii. Although there are methods to calibrate attachment angles of accelerometers, we confirmed that previous methods were not applicable for hammerhead pups. According to raw data, some sharks ascended with a negative angle, which differs from tank observations of captive sharks. In turn, we developed a new method to account for this discrepancy in swimming sharks by estimating the attachment angle from the relationship between vertical speed (m/s) and pitch angle obtained by each accelerometer. The new method can be utilized for field observation of a wide range of species.